Hodnocení zabezpečení obchodních informací - Veselý, Martin (Vysoké učení technické v Brně. Fakulta podnikatelská, 2009)
Diplomová práce „Hodnocení zabezpečení obchodních informací“ je zaměřena na vytvoření metrik pro vyhodnocování zabezpečení informačního systému firmy Tech4sec, spol.s.r.o.. Aplikací metrik jsou v práci stanovena přesná rizika informačního systému firmy a jejich ekonomický dopad. Součástí práce je též vytvoření dílčí části nové IS/IT strategie firmy, jejímž obsahem je odstranění nalezených rizik.

The thesis ”Rating of security business information” is focused on creating metrics in order to assess security of an information system of the company Tech4sec, spol.s.r.o. Risks of the information system and their impact on economy of the company are elaborated by application of the created metrics. To build the part of IS/IT strategy of the company that leads to elimitation of the risks found is dealt with in the thesis as well.
Rating of Security Business Informations
Keywords: zabezpečení informací; informace; data; informační systém; bezpečnost informačního systému; IS/IT strategie; analýza rizik; bezpečnostní politika; rizika informačního systému; šifrování dat; zálohování dat; ochrana dat; metriky zabezpečení; řízení přístupu k informacím; SWOT analýza; stakeholders; security information; information; data; information system; safeguard information system; security information system; IS/IT strategy; risk analysis; security policy; risk of information system; data encryption; data backup; data protection; metrics of security; control of secure access; SWOT analysis; stakeholders